Journalists' memory of Carlos Lacerda: symbolic disputes around press modernization - Medeiros, Fabrício Ferreira de (2023)
Carlos Lacerda (1914-1977) appears in the specialized literature and in the memory of journalists as one of the characters who led the so-called press modernization, that is, the realization of a series of technical, ethical and operational changes developed within the newsrooms around from the 1950s. This article intends to examine the role attributed to Carlos Lacerda and his Tribuna da Imprensa in the modernization process in focus, taking as sources of investigation memory books, articles, editorials and testimonies of journalists who approached aspects of the trajectory of the character after his death on May 21, 1977. As a main conclusion, we highlight the fragmentary character of journalistic memory and the disputes of meaning around Carlos Lacerda's commitment to objective journalism and democratic values ​​and institutions.